Antigen discrimination in primary human T cells - Pettmann, J (2021)
Antigen discrimination is the process by which T cells differentiate self from foreign antigens. They do this using their T cell receptors (TCRs) that recognize peptide antigens bound to major histocompatibility complexes (pMHCs) and this TCR/pMHC interaction is augmented by a host of other co-signaling receptors including adhesion receptors. Despite extensive work, the quantitative ability of T cells to discriminate antigen and the molecular mechanisms underlying it remain debated. We developed an improved binding assay that allowed measurement of ultra-low affinity TCR/pMHC interactions, generated >30 different peptide variants for two different human class I-restricted TCRs and accurately measured their affinities. Surprisingly, we found an affinity floor at a KD of ∼2 mM that could not be further lowered even by changing the peptide sequence dramatically. This could represent the self-pMHC affinity at which T cells are selected during positive selection in the thymus. I utilized the KDs generated by our new binding assay to characterize the ’discrimination power’, which is a measure of a receptor’s ability to discriminate between ligands with different affinities or offrates. I found that the discrimination power of the TCR was much lower than the ’near-perfect discrimination’, previously reported, and that in some settings it was increased by CD2 and LFA-1. Furthermore, these adhesion receptors increased the sensitivity to pMHC, while accelerating pMHC-dependent TCR downregulation, indicating that they likely influence the way the TCR binds pMHC. In the future, this new understanding could be useful for improving the sensitivity and discrimination power of artificial receptor constructs used in immunotherapy, enhancing their safety and efficacy.